Impact of a multidisciplinary quality improvement initiative to reduce inappropriate usage of stress ulcer prophylaxis in hospitalized patients - Choi, Yeo Jin; Sim, Joohyun; Jung, Yun Tae; Shin, Sooyoung (British Journal of Clinical Pharmacology, 2020)
Aims: To promote effective methods to improve overutilization patterns of acid-suppressive therapy in hospitalized patients and to evaluate the impact of multidisciplinary team efforts to reduce inappropriate use of stress ulcer prophylaxis in low-risk patients. Methods: A multidisciplinary quality improvement initiative incorporating education, medication use reviews and reconciliation, and pharmaceutical intervention was implemented in June 2018 for surgical patients hospitalized via emergency department. For the pre-post analysis and time series analysis, patients admitted during April and May were classified into the pre-intervention cohort and those admitted during July and August into the post-intervention cohort. Results: Three hundred and seventeen patients were included in this study (153 and 164 in the pre- and post-intervention cohorts, respectively). The multidisciplinary program was effective in reducing overuse of stress ulcer prophylaxis and healthcare expenses associated with it. Biweekly education on risk factors warranting stress ulcer prophylaxis was provided for clinicians, and acid-suppressive therapy was removed from a preset list of admission orders. The incidence of inappropriate prophylaxis use declined substantially following intervention in overall patients (OR = 0.51, P = 0.01) and a significant decrease was primarily observed among non-ICU patients (OR = 0.50, P = 0.01). Interrupted time series analysis confirmed the significant decline in inappropriate use post intervention (coefficient = −0.63, P < 0.001). The total healthcare expenses associated with such overuse decreased by 58.5% from US$ 19.39 to US$ 8.04 per 100 patient-days. Conclusions: Our multidisciplinary team efforts were associated with improvement in stress ulcer prophylaxis overuse patterns, resulting in a substantial decrease in the incidence of inappropriate use, especially in general wards, and associated healthcare costs.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Anti-Ulcer Agents; Female; Humans; Male; Middle Aged; Peptic Ulcer; Quality Improvement; Retrospective Studies; Ulcer; Young Adult; acid suppression; multidisciplinary; quality improvement; stress ulcer prophylaxis